Global Sport Marketing : Contemporary Issues and Practice. - Desbordes, Michel (Routledge research in sport business and management., 2012)
Globalization has had a profound impact on the sports industry, creating an international market in which sports teams, leagues and players have become internationally recognized brands. This important new study of contemporary sports marketing examines the opportunities and threats posed by a global sports market, outlining the tools and strategies that marketers and managers can use to take advantage of those opportunities. The book surveys current trends, issues and best practice in international sport marketing, providing a useful blend of contemporary theory and case studies from the Ameri.